2017
DOI: 10.1177/0272989x17705637
|View full text |Cite
|
Sign up to set email alerts
|

“Naming and Framing”: The Impact of Labeling on Health State Values for Multiple Sclerosis

Abstract: Introduction: Health state valuation is a key input to many economic evaluations that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Each participant was randomly assigned a set of health states. Previous MSIS-8D surveys had demonstrated that this represented an acceptable workload for participants [11,24]; this was confirmed during pilot testing with people with MS.…”
Section: Valuation Surveysupporting
confidence: 56%
See 1 more Smart Citation
“…Each participant was randomly assigned a set of health states. Previous MSIS-8D surveys had demonstrated that this represented an acceptable workload for participants [11,24]; this was confirmed during pilot testing with people with MS.…”
Section: Valuation Surveysupporting
confidence: 56%
“…Independent t tests were used to determine the ability of the MSIS-8D-P index to distinguish between subgroups of respondents to the valuation survey, based on type of MS and duration since diagnosis. Additional analysis was undertaken using MSIS-8D responses from previous surveys of the general population [11,24] to assess the ability of the MSIS-8D-P index to distinguish between people with and without MS.…”
Section: Discriminative Validitymentioning
confidence: 99%
“…The sociodemographic questions were worded to allow comparison with normative U.K. data (see Table for more details). Respondents were not informed that the health states were cancer‐related, as it has been found previously that the mention of disease labels impacts health state values, probably because prior knowledge or preconceptions of health conditions distort survey participants' values and preferences (Rowen, Brazier, Tsuchiya, Young, & Ibbotson, ; Green, Goodwin, & Hawton, ). Respondents completed the QLU‐C10D prior to the DCE tasks that familiarised respondents with the classification system.…”
Section: Methodsmentioning
confidence: 99%
“…The naming of health conditions or types of disability (for example, using the term 'dementia') may have encouraged the introduction by participants of external knowledge and points of reference, but it is reasonable to expect that when providing proxy responses for an actual close person, the proxy rater would be aware of their health constraints and diagnoses. Previous quantitative research has found that labelling health states influences health state valuation [19,20]; clearly the context and methodologies differ, but the qualitative evidence from this study of proxy raters introducing external considerations relating to a particular illness/diagnosis may be relevant to those undertaking future research involving health state valuation and choosing whether to label health states.…”
Section: Discussionmentioning
confidence: 84%